Exposure of chlorothalonil and acetamiprid reduce the survival and cause multiple internal disturbances in Apis mellifera larvae reared in vitro - Lu, Ying; Gao, Jing; Wu, Tong; Han, Bo; Qian, Bingnan; Shi, Min; Yang, Sa; Diao, Qingyun; Bu, Chunya; Dai, Pingli (Frontiers in Physiology, 2023)
Despite many studies have revealed that honey bee (Apis mellifera L.) larvae are posting a high risk on exposure to pesticides, but the toxicology information on bee larvae remain limited. Here, we test chronic toxicity of chlorothalonil and acetamiprid to honeybee larvae. After continuously fed with different chlorothalonil (1, 2, 4, 8 and 16 μg/mL) or acetamiprid solutions (0.5, 1, 2, 4 and 8 μg/mL), we determined the no observed adverse effect concentration (NOAEC) of chlorothalonil and acetamiprid were 4 μg/mL and 2 μg/mL, respectively. Except for CarE, the enzymic activities of GST and P450 were not influenced by chlorothalonil at NOAEC, while chronic exposure to ACE slightly increased the activities of the three tested enzymes at NOAEC. Further, the exposed larvae showed significantly higher expression of genes involved in a series of different toxicologically relevant process following, including caste development (Tor (GB44905), InR-2 (GB55425), Hr4 (GB47037), Ac3 (GB11637) and ILP-2 (GB10174)), immune system response (abaecin (GB18323), defensin-1 (GB19392), toll-X4 (GB50418)), and oxidative stress response (P450, GSH, GST and CarE), suggesting that more important synergistic and behavioral effects that can affect larvae fitness should be explored in the further.